Stress Management in the two most well-known intensive labor oriented shrimp processing factories of Khulna city, Bangladesh (Global Journal of Management and Business Research, 2012)
Workplace stress is a frequent setback facing most of the cases by the managers at all levels in all types of organization. Although stress is inherent in life and human workplace stress is not confined to the workplace, but it is frequently brought home as well increasingly, employers, trade unions, and health and safety representatives at work are finding guidance on the nature and causes of the problem and on the organizational requirements relating to its prevention and control. A number of factors are considered here , for example, the multidimensionality of the nature of workplace stress, the definition of stress, the direct relationship between stress and behavior, coping with stress and the diversified stress management strategies taken by the management of different organization. In labor oriented shrimp processing factories the promptness of stress very common and in the light of those incidents the stress handling strategies are taken accordingly.
Keywords: Stress; stressor; workplace stress; stress management; satisfaction level